Relative extent of triple Auger decay in CO and CO2. Issue 19 (30th April 2019) - Hult Roos, A.; Eland, J. H. D.; Andersson, J.; Wallner, M.; Squibb, R. J.; Feifel, R.
Abstract : Systematic measurements on single and triple Auger decay in CO and CO2 after the creation of a C 1s or a O 1s core vacancy show that the percentage of triple Auger decay is on the order of 10 −2 of the single Auger decay in these molecules. Abstract : Systematic measurements on single and triple Auger decay in CO and CO2 after the creation of a C 1s or a O 1s core vacancy show that the percentage of triple Auger decay is on the order of 10 −2 of the single Auger decay in these molecules. The fractions of triple Auger decay are compared with triple Auger fractions for carbon atoms and some noble gas atoms, and are found to follow a linear trend correlated to the number of valence electrons on the atom with the initial core vacancy and on its closest neighbours. This linear trend for the percentage of triple Auger decay is represented by a predictive equation TA = 0.13·Nve − 0.5.